Intergenerational programming during the pandemic: Transformation during (constantly) changing times. (7th August 2022) - Jarrott, Shannon E.; Leedahl, Skye N.; Shovali, Tamar E.; De Fries, Carson; DelPo, Amy; Estus, Erica; Gangji, Caroline; Hasche, Leslie; Juris, Jill; MacInnes, Roddy; Schilz, Matthew; Scrivano, Rachel M.; et al.
Abstract: Intergenerational programs have long been employed to reduce ageism and optimize youth and older adult development. Most involve in‐person meetings, which COVID‐19 arrested. ​​Needs for safety and social contact were amplified during COVID‐19, leading to modified programming that engaged generations remotely rather than eliminating it. Our collective case study incorporates four intergenerational programs in five US states prior to and during COVID‐19. Each aims to reduce ageism, incorporating nutrition education, technology skills, or photography programming. Authors present case goals, participants, implementation methods, including responses to COVID‐19, outcomes, and lessons learned. Technology afforded opportunities for intergenerational connections; non‐technological methods also were employed. Across cases, programmatic foci were maintained through adaptive programming. Community partners' awareness of immediate needs facilitated responsive programming with universities, who leveraged unique resources. While new methods and partnerships will continue post‐pandemic, authors concurred that virtual contact cannot fully substitute for in‐person relationship‐building. Remote programming maintained ties between groups ready to resume shared in‐person programming as soon as possible; they now have tested means for responding to routine or novel cancellations of in‐person programming. Able to implement in‐person and remote intergenerational programming, communities can fight ageism and pursue diverse goals regardless of health, transportation, weather, or other restrictions.